Pharmacological Evaluation of Amikacin in Neonates - Howard, Jorge B. (1975)
The in vitro bacterial susceptibilities and pharmacokinetic properties of amikacin (BB-K8) were studied in newborn infants. Gram-negative bacteria and Staphylococcus aureus isolated from neonates were uniformly susceptible to 10 μg or less of amikacin per ml, and five Escherichia coli strains resistant to kanamycin were inhibited and killed by 5 μg or less of amikacin per ml. Mean peak serum concentrations of 17 to 20 μg/ml were observed 30 min after 7.5-mg/kg amikacin doses, and accumulation of drug in serum was not detected after repeated doses for 5 to 7 days. Intravenous infusion of amikacin over a 20-min period resulted in extremely low peak serum levels in four of eight infants studied. Serum half-life values were correlated inversely with postnatal age and renal clearances of amikacin. The volumes of drug distribution indicate that amikacin remains primarily in the extracellular fluid space of neonates. The lack of efficacy and safety data preclude the use of amikacin in neonates at this time.